An empirical study on the influencing mechanism of Chinese university teachers’ wellbeing - Pei, Shuimei; Chen, Zhaojun; Zhang, Xingxia; Guo, Jianpeng (Frontiers in Psychology, 2022)
Current studies on teachers’ wellbeing are mainly on lowering stress or burnout. Few studies have noted that faculty wellbeing is related to teaching activities. Teaching engagement and teaching experience are important predictor variables of teachers’ wellbeing, but the internal and external influencing mechanisms of teachers’ wellbeing have not been clearly revealed. Based on the survey data of 7,408 teachers from 271 undergraduate colleges and universities across China, the internal and external influencing mechanisms of teaching engagement and teaching experience on teachers’ wellbeing were investigated through multicluster structural equation modeling. The results were that teachers’ wellbeing was influenced by both teaching engagement and teaching experience. Among teaching engagement, teachers’ pre-class preparation and post-class communication positively influenced teaching experience, but in-class delivery negatively influenced teaching experience. Teaching experience partially mediates the relationship between engagement and wellbeing. At the level of internal influence, the more teachers identify with and feel accomplished by teaching, the more they invest time and energy in teaching; at the level of external influence, the school environment, leadership, and colleague support affect teachers’ wellbeing through the teaching experience. Universities should offer good teaching hardware and software for teachers, provide adequate teaching support, especially encourage teacher-student communication after class, weaken the rigid constraints and controls on teachers’ teaching in class, give teachers enough teaching autonomy, and reduce their teaching burden to inspire teachers to be more actively involved in teaching, improve their teaching experience, and thus enhance their sense of wellbeing.